CHARACTERIZATION OF BACTERIAL PATHOGEN CAUSING WILT AND LEAF BLIGHT ON CORN (Zea mays) BY PHYSIOLOGICAL, BIOCHEMICAL AND MOLECULAR METHODS - suryani, Lilis; Aini, Luqman Qurata; Sugiharto, Ariffin Noor; Abadi, Abdul Latief (AGRIVITA, Journal of Agricultural Science, 2012)
In 2011, we found a new bacterial disease characterized by wilt, dwarf and blight symptoms on sweet corn in Batu, East Java, Indonesia. The objective of this study is to characterize the causal agent of the disease. In this study, several assays were conducted, including hypersensitive response, pathogenicity, physiological and biochemical characteristics, PCR detection Â using two specific species primer pairs for Pantoea stewartii pv. stewartii, and homology analysis of 16S rRNA gene sequence. Four Gram-negative, non-motile, facultative anaerobic bacteria were isolated from the diseased tissue. Only two strains, BD1 and BB2, gave positive result in hypersensitive reaction, pathogenicity, and Kochâs postulate assays. BB2 and BD1 strains also showed positive results in the PCR amplification using specific primers derived from the P. stewartii subsp. stewartii 16-23S gene region of but showed negative result when using primers derived from P. stewartii subsp. stewartii hrpS gene region. Sequence of partial 16S rRNA gene of BD1 and BB2 showed highest homology at 96%Â  to P. stewartii subsp. stewartii strain ATCC 8199 (NR. 044800.1). This results suggest that bacterial pathogens isolated from sweet corn in Batu were strains of Â Pantoea spp. Keywords : Zea mays, Pantoea spp, wilt, leaf blight, PCR